A Review of The Place of Adipose-Derived Stem Cells among Stem Cell Applications in Neurodegenerative Diseases - Yigitturk, Gurkan; Cavusoglu, Turker (Current Topics in Medicinal Chemistry, 2025)
Treatment of neurodegenerative diseases aims to slow disease progression, alleviate symptoms, and improve life quality. Adipose<span class=
Keywords: regenerative medicine